COMPARATIVE ANALYSIS OF SOCIAL SERVICES PROVIDED TO FEMALE COMBATANTS AND VETERANS IN UKRAINE AND ABROAD - Faidiuk, Olena; Liakh, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The war in Eastern Ukraine has been going on since 2014. This situation has led to new challenges for the social sphere, in particular, the construction of a system of social services for combatants and veterans. Female combatants and veterans need gender-specific services adopted to this particular category. Since the experience of social assistance to this specific category of clients of social work in Ukraine is limited, there is a need to study the experience of other countries to address the issue.The purpose of the article is to analyze the peculiarities of women's military service and the system of social protection of this category in Ukraine and abroad.The article analyzes the experience of Australia, Israel, Spain, Canada, Korea, Poland, the USA, and Croatia in implementing the policy of social protection of combatants. The authors identify the main types of services and assistance to this category provided by the legislation in other countries.The authors of the article used the method of theoretical analysis of scientific works and legal documents that describe and regulate the mechanism of social protection of servicemen/servicewoman in different countries; compare the key aspects and features of women's military service in different countries and systematize the list of social services and structures responsible for providing various social services.